ESTUDO DA EFICÁCIA ADAPTATIVA DE HERDEIROS DE EMPRESA FAMILIAR - Sooma, Renata (2005)
The present work focuon studying the adaptative efficiency of familial company heirs, second to the Adaptation Theory of Ryad Simon. The objectives were: 1. investigate the adaptative efficiency of familial company heirs; 2. describe the aspects of the adaptative dynamics of the heirs; 3. describe the aspects of the familial dinamic internalized by the heirs of each family; 4. investigate the repercussions obtained by the analysis of the adaptative efficiency of each heirs in the familial company context. The method used was clinic, and the technique called the preventive clinic interview. Seven heirs of two different familial companies were interviewed, being that all of them work at them. The data of the interviews have been clinically assessed by the Operable Adaptive Diagnostic Scale OADS - and factor analysis, second to the Adaptation Evolution Theory by Ryad Simon. The results found were: 72% (5 heirs) have been classified in group 4 Severe Ineffective Adaptation; 14% (1 heir) in group 5 - Grave Ineffective Adaptation, and 14% (1heir) in group 3 Moderate Ineffective Adaptation in Crisis. In the analysis of the results, it has been verified that importance of the Affective-Relational area, 100% of the heirs were classified with highly inadequate answers and the one who balanced the different classifications, mentioned above, was in Productivity area. Coming to this diagnostic we could perceive the importance of the relationship with the father figure, present both at home and company. In the analysis of the heirs and the dynamic of the two families, it was concluded that when the father figure behaves in an omnipotent and non replaceable way, then the children are not allowed to grow up and search for satisfaction in what they produce, different from when this father is able to set boundaries, but more steadily, delegating responsibilities to his children, demostrating trustworthifulness on them. This posture facilitate the reach of satisfaction in the Productivity area. In this study it has become evident that the familial dynamic extend itself until the enterpreneurial one so that in one of these families, whose father was able to delegate to this children the control over the company, the dynamic in the enterprise seems to be healthy, permeated by constructive impulses. As for the other, whose father maintains the control, it seems to be very sick, being the destructive impulses in majority, which is spread to the company a well.